Comparing ceramic technologies: The production of Terra Sigillata in Puteoli and in the Bay of Naples. (February 2019) - Grifa, Celestino; Germinario, Chiara; De Bonis, Alberto; Langella, Alessio; Mercurio, Mariano; Izzo, Francesco; Smiljanic, Danijela; Guarino, Vincenza; Di Mauro, Simone; Soricelli, Gianluca
Abstract: Archaeological excavations carried out in the sites of Rione Terra and Via Fascione in Pozzuoli (ancient Puteoli, Italy) unearthed samples of Red Slip Ware attributed to Terra Sigillata from Puteoli and Produzione A della Baia di Napoli, which are among the most important ceramic classes produced in Campania region and circulating in the Roman Empire from the 1st century BCE. Archaeometric analyses performed on twenty-one samples highlighted that stylistic and typological features are connected to technological ones, permitting to clearly distinguish the two different productions. The samples of Terra Sigillata showed fine-grained ceramic bodies, high-CaO content (on average 15.6 wt%), abundant micro-fossils along with quartz, feldspar and micas. The thin red slip, present on both inner and outer surfaces, appears sintered and well preserved. Sintering degree and mineralogical assemblages suggest that the artefacts experienced high firing temperatures (often exceeding 900 °C). On the other hand, the Produzione A samples contain a lower micro-fossils amount and rare volcanic grains. The vessels are covered by a thinner and non-sintered red slip compared to that of Terra Sigillata . Mineralogy and microstructures of the ceramic bodies also suggested lower firing temperatures (850–900 °C). Then, the technology and the exploited clayey raw material were different in the production areas probably highlighting different cultural influences as well as different commercial paths. Finally, the comparison with available data on italic Red Slip Ware allowed us to find some key-parameter for discerning the most important production areas. Highlights: Archaeometric approach was adopted for the study of Campanian Terra Sigillata . High-quality production of Terra Sigillata developed in Puteoli Fast firing procedures were adopted for the Produzione A pottery. The exploitation of two different high-CaO clayey deposits was inferred. Compositional key-differences with other italic Red Slip Wares were defined.